2018
DOI: 10.25135/rnp.38.17.08.135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Wound Healing Properties of Luteolin Ointments on Excision and Incision Wound Models in Diabetic and Non-Diabetic Rats

Abstract: Luteolin, which is structurally classified under the flavonoids, is naturally distributed abundant among medicinal plants, vegetables and fruits. The wound healing effects of Luteolin ointments were evaluated for incision and excision wound models on non-diabetic and Streptozotocin induced diabetic rats by using macroscopical, biomechanical, biochemical and histopathological methods. Two different concentrations (0.5 % and 1 % (w/w)) of the Luteolin ointment were prepared with the mixture of glycol stearate:pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In silico, in vitro, in vivo studies and a clinical trial with a formulation containing luteolin has shown that luteolin has great therapeutic effect against inflammation-associated disturbances. In addition, the effects of luteolin ointment on the key steps of wound healing, such as cell proliferation, cell migration and collagen deposition, have been proven in previous reports [74,75].…”
Section: Resultsmentioning
confidence: 86%
“…In silico, in vitro, in vivo studies and a clinical trial with a formulation containing luteolin has shown that luteolin has great therapeutic effect against inflammation-associated disturbances. In addition, the effects of luteolin ointment on the key steps of wound healing, such as cell proliferation, cell migration and collagen deposition, have been proven in previous reports [74,75].…”
Section: Resultsmentioning
confidence: 86%
“…Similar results were achieved in a wound model using diabetic and non‐diabetic rats. Luteolin treatment resulted in faster wound healing with a higher tensile strength, more collagen, a better epithelial regeneration and less inflammation 60 …”
Section: Wound Healingmentioning
confidence: 99%
“…f. (SK) and Salvia euphratica Montbret, Aucher & Rech. f. var, showing strong wound healing effects with important antimicrobial and antioxidant activities Luteolin (Arachis hypogaea L), naturally distributed among medicinal plants, vegetables and fruits, structurally rich in flavonoids, was tested to evaluate wound healing in diabetic and non-diabetic Wistar rats, through topical applications of the formulation in the wounds, showing that flavonoids increase the formation of collagen fibrils in the tissues of non-diabetic and diabetic wounds, since the phenolic compounds present, known as potent antioxidants, contribute to the process of accelerating healing (Ozay et al, 2018).…”
Section: Discussionmentioning
confidence: 99%